Peran Bisnis Syariah dalam Membentuk Jiwa Kewirausahaan Islami - Rosdita Indah Yuniawati; Aep Syaeful Millah (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to analyze the role of Islamic business in shaping an Islamic entrepreneurial spirit. This research uses a qualitative method with a library research approach. This data collection technique involves analyzing, reading, and studying all relevant information related to the issue being studied or researched from e-books, manuscripts, books, journals, theses, and other similar materials. This approach examines various academic references related to the principles of Islamic business and the characteristics of Islamic entrepreneurship. The results show that Islamic business is not solely oriented towards material profit, but also emphasizes moral and spiritual values ​​, such as honesty, justice, trustworthiness, balance, and mutual assistance, as key principles in conducting business activities. These values ​​shape the character of Muslim entrepreneurs who are imbued with integrity, responsibility, and honesty, and who utilize business activities as a means of worship and for the benefit of the community. The integration of Islamic business principles and Islamic entrepreneurship can create an ethical, productive, and sustainable business ecosystem